2024
DOI: 10.3390/biomedicines12020337
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Dermatological Dilemmas and Endocrinological Complexities: Understanding Necrobiosis Lipoidica—A Comprehensive Review

Corina Ionescu,
Aida Petca,
Mihai Cristian Dumitrașcu
et al.

Abstract: Background: Necrobiosis lipoidica (NL) is a rare granulomatous skin disorder with a predilection for females, often associated with diabetes mellitus (DM). This paper aims to comprehensively review the literature on NL, focusing on its association with DM, thyroid disorders, and the metabolic syndrome. Methods: A systematic search was conducted in English-language literature from inception to October 2023, utilizing PubMed. We identified 530 studies and selected 19 based on clinical significance, statistical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…In this regard, a recent multicenter retrospective study, examining the data of 52 patients with NL of the lower legs, found a prevalence of thyroid function disorders in 13%, compared to 5.5% in the general population, suggesting that NL could be associated with other conditions than DM alone [7]. It was observed that patients diagnosed with both NL and type 1 DM had a higher overall susceptibility to celiac disease in comparison to those with diabetes alone, with the prevalence of celiac disease being 3.4% among patients with both conditions, compared to 1% among patients with type 1 DM [8,9]. In addition to DM, NL patients have also been observed to suffer from dyslipidemia, obesity, hypertension, coronary heart disease, stroke, and reduced renal function, with hypertension being the most frequent secondary diagnosis associated with NL [10].…”
Section: Introductionmentioning
confidence: 97%
“…In this regard, a recent multicenter retrospective study, examining the data of 52 patients with NL of the lower legs, found a prevalence of thyroid function disorders in 13%, compared to 5.5% in the general population, suggesting that NL could be associated with other conditions than DM alone [7]. It was observed that patients diagnosed with both NL and type 1 DM had a higher overall susceptibility to celiac disease in comparison to those with diabetes alone, with the prevalence of celiac disease being 3.4% among patients with both conditions, compared to 1% among patients with type 1 DM [8,9]. In addition to DM, NL patients have also been observed to suffer from dyslipidemia, obesity, hypertension, coronary heart disease, stroke, and reduced renal function, with hypertension being the most frequent secondary diagnosis associated with NL [10].…”
Section: Introductionmentioning
confidence: 97%